Android programming : the Big Nerd Ranch guide - Phillips, Bill (Software engineer); Stewart, Chris; Marsicano, Kristin (Big Nerd Ranch, 2017)
Android Programming: The Big Nerd Ranch Guide is an introductory Android book for programmers with Java experience. Based on Big Nerd Ranch's popular Android bootcamps, this guide will lead you through the wilderness using hands-on example apps combined with clear explanations of key concepts and APIs. This book focuses on practical techniques for developing apps compatible with Android 4.4 (KitKat) through Android 7.0 (Nougat) and beyond. Write and run code every step of the way, using Android Studio to create apps that integrate with other apps, download and display pictures from the web, play sounds, and more. Each chapter and app has been designed and tested to provide the knowledge and experience you need to get started in Android development.